STUDI LITERASI KIMIA SISWA SEKOLAH MENENGAH KEJURUAN PADA MATERI ZAT DAN PERUBAHAN - Norma Eralita; Yudi Agus Setiawan (Universitas Labuhanbatu, 2022)
Scientific literacy consists of four dimensions (aspects) namely knowledge or science content, scientific context, competence (scientific process) and attitudes. This study aims to determine the ability of chemical literacy in the aspects of knowledge, context, competence and attitudes in vocational high school students. The research method used is quantitative description method. The sample used was 50 students of class X SMK N 1 Kutasari. The data collection technique in this study was in the form of a questionnaire with a Likert scale. Based on the results obtained from the research that has been done, it is 71.5%. This shows that the students' chemical literacy skills on material and its changes are still in the medium category. With each aspect obtained a percentage of: 72% Knowledge, 69% Context, 70% Competence, 75% Attitude.Keywords: Chemical Literacy; Substance and Change; Aspects